Modelling of dust generation, transport and remobilization in full-metal fusion reactors. (1st April 2022) - Ratynskaia, S; Vignitchouk, L; Tolias, P
Abstract: The design, licensing and operation of magnetic confinement fusion reactors impose various limitations on the amount of metallic dust particles residing inside the plasma chamber. In this context, predictive studies of dust production and migration constitute one of the main sources of relevant data. These are mainly conducted using dust transport codes, which rely on coupled dust-plasma and dust-wall interaction models, and require external input on the dust and droplet initial conditions. Some particularities of dust modelling in reactor-relevant conditions are analyzed with an emphasis on dust generation mechanisms relevant for disruption scenarios and on dust remobilization mechanisms relevant for ramp-up scenarios. Emerging topics such as dust production by runaway electron impact and pre-plasma remobilization of magnetic dust are also discussed.